Phenolic Compounds and Anthocyanins in Legumes and Their Impact on Inflammation, Oxidative Stress, and Metabolism: Comprehensive Review - Rocio Guadalupe Hernández-Ruiz; Xochitl Citalli Olivares-Ochoa; Yahatziri Salinas-Varela; David Guajardo-Espinoza; Luis Gustavo Roldán-Flores; Edgar Alfonso Rivera-Leon; Andres López-Quintero (Molecules)
Inflammation, oxidative stress, and metabolic diseases are intricately linked in a complex, self-reinforcing relationship. Inflammation can induce oxidative stress, while oxidative stress can trigger inflammatory responses, creating a cycle that contributes to the development and progression of metabolic disorders; in addition, these effects can be observed at systemic and local scales. Both processes lead to cellular damage, mitochondrial dysfunction, and insulin resistance, particularly affecting adipose tissue, the liver, muscles, and the gastrointestinal tract. This results in impaired metabolic function and energy production, contributing to conditions such as type 2 diabetes, obesity, and metabolic syndrome. Legumes are a good source of phenolic compounds and anthocyanins that exert an antioxidant effect—they directly neutralize reactive oxygen species and free radicals, reducing oxidative stress. In vivo, in vitro, and clinical trial studies demonstrate that these compounds can modulate key cellular signaling pathways involved in inflammation and metabolism, improving insulin sensitivity and regulating lipid and glucose metabolism. They also exert anti-inflammatory effects by inhibiting proinflammatory enzymes and cytokines. Additionally, anthocyanins and phenolics may positively influence the gut microbiome, indirectly affecting metabolism and inflammation.